Literature Riview: Kekurangan Energi Kronis Sebagai Faktor Risiko Terjadinya Anemia Pada Ibu Hamil - Dayu Cindy, Ida Ayu Cindy Paramitha; Adi Wibowo (LPPM ITEKES Mahardika, 2025)
Pregnancy causes a significant increase in macro- and micronutrient requirements, so nutritional fulfillment is key in maintaining maternal and fetal health. Chronic energy deficiency (CED) is one of the most common nutritional problems in pregnant women and acts as a major risk factor for anemia. This literature review aims to determine the relationship between CED and anemia in pregnant women. Data were obtained from 12 articles published in 2015-2025 accessed through Google Scholar and PubMed. The results of the review showed that CED, characterized by upper arm circumference (LiLA) < 23.5 cm, is significantly associated with low hemoglobin levels. Nutrient deficiencies in mothers significantly impair erythropoiesis, increasing the risk of iron deficiency anemia and megaloblastic anemia. Thus, CED is proven to be a major risk factor for anemia in pregnant women and has the potential to cause obstetric and neonatal complications. Early detection and appropriate nutritional interventions are essential for prevention.